Amaryllididae and Lysianassidae (Amphipoda: Lysianassoidea) from off the central coast of Brazil (11oS-22oS), with descriptions of three new species - Senna, André R.; Serejo, Cristiana S. (Zootaxa, 2008)
Material collected on the central Brazilian coast from the REVIZEE Benthos Program was analyzed and three new species were herein described. Knowledge about sexual dimorphism on Bonassa is improved. The hypothesis of endemism of the genus Amaryllis to Australia is contested with the discovery of a new species of Amaryllis in the Southwestern Atlantic Ocean. A new species of Lysianassa is described, and its differences to L. brasiliensis are commented too. Lysianopsis concavus Senna, 2007 is herein described with more details in description and figures. The distributions of the described species are given. Keys to identification of Brazilian Lysianassoidea families and Lysianassidae species are presented in this paper.Key-words: Amaryllis, Bonassa, Lysianassa, Lysianopsis, taxonomy, Brazilian province